Atención farmacéutica en la bibliografía nacional e internacional - María Victoria Rojo Manteca (Fundación Pharmaceutical Care España, 2021)
Applications for pharmacogenomics in pharmacy practice: A scoping review Hayashi M, Hamdy DA, Mahmoud SH. Research in Social and Administrative Pharmacy 2021. Article in press.  https://doi.org/10.1016/j.sapharm.2021.08.009  Roles, barriers and behavioral determinants related to community pharmacists' involvement in optimizing opioid therapy for chronic pain: a qualitative study Alenezi A, Yahyouche A, Paudyal V. International Journal of Clinical Pharmacy. 2021. https://doi.org/10.1007/s11096-021-01331-1  Ability to detect potentially inappropriate prescribing in older patients: comparative analysis between PIM‑Check and STOPP/STARTv2  Farhat A, Panchaud A, Al‑Hajje A, Al‑Hajje PO, Csajka C. European Journal of Clinical Pharmacology. 2021, 77:1747-1756 https://doi.org/10.1007/s00228-021-03171-4